DETERMINAN NILAI PERUSAHAAN MARITIM DI INDONESIA - Ardiansyah Ardiansyah; Mohamad Nur Islami; Asri Eka Ratih (AKUNTANSI DEWANTARA, 2023)
The purpose of this study is to find out and obtain empirical evidence regarding the effect of size, profitability and capital structure on firm value with Corporate Social Responsibility as a moderating variable. The object of this research is maritime companies listed on the IDX in 2017-2021. The total sample in this study were 12 sample companies with a total of 55 research observation data that met the criteria for 5 years of observation, through the nonprobability method with purposive sampling technique. The analysis technique of this research uses Moderate Regression Analysis (MRA). Based on the results of the analysis it was found that profitability had a significant positive effect on firm value, profitability and capital structure had a positive and significant effect on firm value. Meanwhile, size and CSR have a negative and significant effect on firm value. Corporate Social Responsibility does not significantly strengthen the effect of size on firm value. Corporate Social Responsibility significantly weakens the effect of profitability on firm value. And Corporate Social Responsibility does not significantly strengthen the effect of capital structure on firm value.